Specyfika antropologii lingwistycznej w myśli Aleksandra Durantiego - Uwaoma, Nwauzor Lambert (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article makes a presentation of the specificity of linguistic anthropology in the thought of Alessandro Duranti. This discussion takes effect within the range of what Durant calls the scope and theoretical concern in contemporary linguistic anthropology. In this discussion however, he presents a new interpretation and definition of human being in the perspective of linguistic anthropology. Thus, man is defined by the functionality of his language, as actualizing his social nature. An elaboration on Duranti’s anthropological proposition which is informed by his approach however, shows some problems. As a way forward, an attempt is made as it becomes necessary to examine his project in the light of the method of realistic metaphysics as cultivated by the Lublin philosophical school. This method or approach provides a working solution which will rather consider language as part of human rationality through which we actualize our social nature.